A Review on the Failure Modes of Rock and Soil Mass under Compression and the Exploration about Constitutive Equations of Rock and Soil Mass - Liansheng Tang; Yuxi Wang; Yinlei Sun; Yang Chen; Zhanlun Zhao (Advances in Civil Engineering)
The constitutive equation of rock and soil has always been the core problem in rock and soil mechanics. Up to now, the nature of nonlinear shear strength of rock and soil has not been revealed. In many engineering practices, it is still considered that the failure mode of rock and soil is always shear failure, and Coulomb linear constitutive equation is adopted, or Mohr envelope is fitted by data. However, the constitutive equation of rock mass is nonlinear, and its failure mode is not only shear failure. A large number of single triaxial tests show that there is not only shear stress, but also tensile stress in the failure process of rock and soil. Theoretical and experimental research on failure mode of rock mass under pressure are one of the important means to improve and develop soil mechanics. It is important to understand the nonlinear nature of rock and soil constitutive equation to explore the energy variation and the distribution of tensile stress and shear stress in different failure modes of rock and soil.